2010
DOI: 10.3382/ps.2009-00495
|View full text |Cite
|
Sign up to set email alerts
|

Selected microbial groups and short-chain fatty acids profile in a simulated chicken cecum supplemented with two strains of Lactobacillus

Abstract: Among the bacterial fermentation end products in the chicken cecum, butyrate is of particular importance because of its nutritional properties for the epithelial cell and pathogen inhibitory effects in the gut. An in vitro experiment, operated with batch bioreactor, was conducted to quantify butyric-producing bacteria in a simulated broiler cecum supplemented with Lactobacillus salivarius ssp. salicinius JCM 1230 and Lactobacillus agilis JCM 1048 during 24 h of incubation. Selected bacterial species were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 23 publications
5
73
0
1
Order By: Relevance
“…Several studies have suggested that the secreted factors from probiotic bacterial growth are likely to be major contributors to the beneficial effects of probiotics, and some active ingredients in probiotic culture supernatant have been identified, including conjugated linoleic acids (14), short-chain fatty acids (35), polyamines (34), peptides (18), proteins (64), polyphosphate (48). These active ingredients have been demonstrated to be effective in the treatment of several intestinal disorders and liver disease through stimulating Gram-positive bacterial growth, changing the intestinal pH, promoting immune function, and inhibiting intestinal barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the secreted factors from probiotic bacterial growth are likely to be major contributors to the beneficial effects of probiotics, and some active ingredients in probiotic culture supernatant have been identified, including conjugated linoleic acids (14), short-chain fatty acids (35), polyamines (34), peptides (18), proteins (64), polyphosphate (48). These active ingredients have been demonstrated to be effective in the treatment of several intestinal disorders and liver disease through stimulating Gram-positive bacterial growth, changing the intestinal pH, promoting immune function, and inhibiting intestinal barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The production of hydrogen peroxide by L. salivarius CECT 5713 has been reported (Martin et al, 2006) and could inhibit the growth of S. aureus through its H 2 O 2 production (Ocana et al, 1999b). The highest antimicrobial activity was against S. paratyphi A but its low inhibitory against S. aureus and inhibitory effect may be due to acid, bacteriocin-like substances (Ocana et al, 1999b) or both in combination with other metabolites such as hydrogen peroxide and short chain fatty acids (Ahrne et al, 2005;Meimandipour et al, 2010). L. salivarius UCC118 is the most cultivated, not only in in vitro assay but also in vivo assay and clinical trials, by which its probiotic function and, particularly, its anti-infl ammatory effects have been demonstrated (Castellazzi et al, 2007;Dunne et al, 1999Dunne et al, , 2001Flynn et al, 2002;McCarthy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that volatile fatty acids such as propionate and butyrate have an influence on the inhibition of pathogenic bacterial flora development [24,25,31,32,[34][35][36] . A higher concentration of those acids was noted in the caecum content from hens fed with zinc as an organic and biological preparation as compared to the inorganic form.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial fermentation leads to the formation of SCFAs, which are necessary in the metabolism of the intestine epithelium [32] . The acetic acid is characterised by the lowest energy value (0.876 MJ/mol) as compared to the propionate (1.536 MJ/mol) and the butyrate (2.194 MJ/mol), and their mutual ratio plays a role in determining the amount of energy delivered to the organism [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation